2022
DOI: 10.3390/healthcare10122406
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ eMental Health Literacy and Risk of Diagnosis with Mental Health Disorders

Abstract: Background: This study investigated college students’ eMental health literacy (eMHL), knowledge of common mental disorders and risk of being diagnosed with a mental health disorder and compared their knowledge of mental disorders and concurrent risk of diagnosis with high and low eMHL; Method: A total of 123 college students completed an online survey through Amazon’s Mechanical Turk (MTurk). Data were analyzed using descriptive statistics and chi-square tests; Results: eMental health literacy scores were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
(69 reference statements)
0
2
1
Order By: Relevance
“…However, the results are not consistent with the results of Cormier et al [23] who reported desired levels of mental health literacy among students. Considering the higher level of mental health literacy among students with older years [23], it could be said that the presence of graduate students and students with higher educational levels, as well as the use of different tools to measure mental health literacy, could be possible reasons for the difference between the results of the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the results are not consistent with the results of Cormier et al [23] who reported desired levels of mental health literacy among students. Considering the higher level of mental health literacy among students with older years [23], it could be said that the presence of graduate students and students with higher educational levels, as well as the use of different tools to measure mental health literacy, could be possible reasons for the difference between the results of the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Leftover drug at home also provides easy access when one experiences similar symptoms [25]. This is concerning because self-medication can lead to serious consequences [26].…”
Section: Mishra Et Almentioning
confidence: 99%
“…Studies on eMHL have primarily focused on younger populations. For instance, Cormier et al [ 18 ] found a close relationship between low eMHL and an increased risk of mental health problems. Another study on young adults found that those with low eMHL are at high risk of experiencing a mental health disorder [ 19 ].…”
Section: Introductionmentioning
confidence: 99%